Outpatient prescription drug spending by the Medicare population - Waldo, Daniel R. (CENTERS for MEDICARE & MEDICAID SERVICES, 1987)
Legislation proposed in the 100th Congress and debated during the summer of 1987 would cover prescription drug spending by Medicare enrollees after the enrollee had met a deductible. However, at the time that the legislation was proposed, there were no comprehensive estimates of the extent of current expenditures for prescription drugs by that population, nor of the expected cost of the proposed coverage. In this article, the author estimates “current-law” drug spending by Medicare enrollees. A distribution around the average expenditure is developed, demonstrating the proportion of users that exceed any given annual expenditure and the proportion of total expenditures comprised by spending in excess of that “deductible.”